Design Of Crack Detection System Software For IC Package Using Blob Analysis And Neural Network. - Samad, Rosdiyana; Arshad, Mohd Rizal; Samad, Zahurin (2005)

(untitled)
In this research, three methods for the detection of crack defects on integrated circuit (IC) packages are proposed. These methods use blob analysis technique in image processing stage, and use multi-layered perceptron (MLP) neural network to classify the IC package.